Ultra-processed foods consumption and health-related outcomes: a systematic review of randomized controlled trials - Aramburu, Adolfo (2024)
Introduction: The increase in ultra-processed foods (UPFs) intake has raised concerns about its impact on public health. Prospective observational studies have reported significant associations between higher intake of UPFs and adverse health outcomes. The aim of this study is to determine whether these associations could be confirmed in randomized controlled trials (RCTs). Methods: We conducted a systematic review to analyze the evidence on the effects of UPFs intake on health. A systematic search was conducted in Medline, Embase, Web of Science, Scopus, LILACS, and CENTRAL up to April 22, 2024. RCTs in English, Spanish, and Portuguese evaluating the health effects of interventions to modify UPFs intake were included. The certainty of evidence was determined using the GRADE methodology. Results: Three educational intervention studies and one controlled feeding trial were included, evaluating the effect of reducing the consumption of UPFs (455 participants, median follow-up, 12 weeks). No significant effects were observed in 30 out of the 42 outcomes evaluated. The controlled feeding trial in adults with stable weight showed a reduction in energy intake, carbohydrates, and fat (low certainty of evidence), as well as in body weight, total cholesterol, and HDL cholesterol (moderate certainty of evidence). In the educational intervention studies, a reduction in body weight and waist circumference was observed (low certainty of evidence) in women with obesity, as well as improvement in some dimensions of quality of life (very low certainty of evidence). No significant changes were observed in children and adolescents with obesity, while in overweight pregnant women, the consumption of UPFs was not reduced, so the observed benefits could be attributed to other components of the intervention. Conclusion: Interventions aimed at reducing the consumption of UPFs showed benefits on some anthropometric and dietary intake outcomes, although significant effects were not observed for most of the evaluated outcomes. The limited number and significant methodological limitations of the studies prevent definitive conclusions. Further well-designed and conducted RCTs are needed to understand the effects of UPF consumption on health. Systematic review registration: https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023469984